2010
DOI: 10.1111/j.1365-3121.2010.00983.x
|View full text |Cite
|
Sign up to set email alerts
|

When an ‘inverse’ fabric is not inverse: an integrated AMS‐SPO study in MORB‐like dykes

Abstract: Terra Nova, 23, 49–55, 2011 Abstract Magma flow direction is recorded in the macroscopic mineral petrofabric and magnetic fabric of the MORB‐like Rooi Rand dyke swarm. The bulk magnetic fabric is sub‐parallel to the dyke plane, resulting from preferred orientation of grains during magma flow. This is referred to as type‐A fabric. A study of mineral shape preferred orientation reveals an additional fabric, which is orthogonal to the average dyke orientation in 30% of the data. This fabric is carried by both pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In oblate fabrics, the planar elements of the magnetic fabric dominate and the shape of the susceptibility ellipsoid is flattened in the K 1 – K 2 plane. If the fabric elements at a site are strongly oblate and the 95% confidence ellipses of the K 1 and K 2 axes overlap in the K 1 − K 2 plane, then the K 1 orientation must be treated with caution [ Hastie et al ., ]. Hastie et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In oblate fabrics, the planar elements of the magnetic fabric dominate and the shape of the susceptibility ellipsoid is flattened in the K 1 – K 2 plane. If the fabric elements at a site are strongly oblate and the 95% confidence ellipses of the K 1 and K 2 axes overlap in the K 1 − K 2 plane, then the K 1 orientation must be treated with caution [ Hastie et al ., ]. Hastie et al .…”
Section: Resultsmentioning
confidence: 99%
“…Hastie et al . [], however, showed that the K 1 lineation may provide information on the flow fabric in planar intrusions even when the magnetic fabrics are oblate and inverse. When the confidence ellipses of K 1 and K 2 axes do not overlap, the K 1 orientation may reflect a flow or stretching direction.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic fabric may easily reveal mineral distributions that show an imbrication of the magnetic lineation and/or magnetic foliation with respect to the dyke margins, which may be used to infer the sense of flow, as shown in Figure 2. This approach is widely used in the literature to determine magma flow within dykes (Knight & Walker 1988;Varga et al 1998;Aubourg et al 2002;Geoffroy et al 2002;Porreca et al 2006;Soriano et al 2008;Silva et al 2010), even though it is not adopted for all cases (Kissel et al 2010;Hastie et al 2011aHastie et al , b, 2013. This ideal situation may be complicated by the occurrence of …”
Section: Methods and Laboratory Analysesmentioning
confidence: 99%
“…In particular, amphibole phenocrysts and vesicles orientations were statistically treated by means of the image analysis of photographs taken in these natural sections in different orientations, either parallel or orthogonal to the dyke plan (Launeau et al 2010). The SPO technique is widely used for studying rock fabric and is generally applied to microscopic images (thin section and SEM images) when several cases of 'inverse' magnetic fabric are recognized in the samples (Archanjo et al 2002;Launeau et al 2010;Hastie et al 2011a, b and references therein). In our case, except for a very few specimens, most of the AMS data show a 'normal' fabric: that is, with magnetic foliation (K max 2 K int ) parallel to the dyke plane.…”
Section: Methods and Laboratory Analysesmentioning
confidence: 99%
“…In this case, additional investigations of the magnetic mineralogy and other independent observations are necessary to understand its origin (e.g. Archanjo et al 2002;Chadima et al 2009;Kissel et al 2010;Hastie et al 2011).…”
Section: Anisotropy Of Magnetic Susceptibility (Ams) As Magmatic Flowmentioning
confidence: 99%